2021
DOI: 10.1523/eneuro.0044-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Stress Controllability Modulates Basal Activity of Dopamine Neurons in the Substantia Nigra Compacta

Abstract: Prolonged stress induces neural maladaptations in mesolimbic dopamine (DA) system and produces emotional and behavioral disorders. However, the effects of stress on activity of DA neurons are diverse and complex that hinge on the type, duration, intensity, and controllability of stressors. Here, controlling the duration, intensity, and type of the stressors to be identical, we observed effects of stressor controllability on the activity of substantia nigra compacta (SNc) DA neurons in mice. We found that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…On the other hand, behavioral sensitization to amphetamine was observed in food-restricted D2 but not B6 mice [ 78 ], whereas mice of both strains developed amphetamine-induced behavioral sensitization [ 41 ]. Moreover, repeated exposure to prolonged inescapable and unavoidable stress was reported to reduce responsivity of mesencephalic DA neurons to a natural reward in B6 mice [ 79 ]. Therefore, although restricted feeding fosters accumulation of FosB and ΔFosB within the mesencephalon of mice from both strains, this phenotype could be associated with different strain-specific neuroadaptation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, behavioral sensitization to amphetamine was observed in food-restricted D2 but not B6 mice [ 78 ], whereas mice of both strains developed amphetamine-induced behavioral sensitization [ 41 ]. Moreover, repeated exposure to prolonged inescapable and unavoidable stress was reported to reduce responsivity of mesencephalic DA neurons to a natural reward in B6 mice [ 79 ]. Therefore, although restricted feeding fosters accumulation of FosB and ΔFosB within the mesencephalon of mice from both strains, this phenotype could be associated with different strain-specific neuroadaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Role of DAergic neurotransmission in anxiogenic and depressive behaviours is well established (Dong et al, 2020;Baik, 2020). Whereas, stress effects on DAergic neuronal activity is complicated which possibly depends on following features; type, duration, intensity, and controllability of stressors (Yao et al, 2021). The current study revealed subsequent unpredictable stress increased DA and its metabolite DOPAC in rat brain.…”
Section: Discussionmentioning
confidence: 54%
“…The widely used rodent model of unpredictable stress, mimic behavioral traits monitored in patients with anxiety, depression and related mood disorders, involves systematic and repeated exposure to intermittent series of unpredictable stressors lasting days or weeks (Sequeira-Cordero et al, 2019). The role of dopaminergic (DAergic) neurons has been the focus of attention in stress-induced maladaptation of critical brain circuits that produce major depressive disorders and anxiety problems (Yao et al, 2021). Moclobemide, a reversible inhibitor of type A monoamine oxidase (MAO) is common antidepressant and extensively recommended worldwide to counteract neurodegenerative diseases with fewer undesirable side effects (Nowakowska et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This learning and updating depend on the modulatory influence of local dopamine (DA) release in the cortico-striatal pathway [5,6]. Stress can alter dopamine neurotransmission in the striatum in both DMS and in the dorsolateral striatum (DLS) and alter the ability of animals to adapt flexibly when A-O associations change [7][8][9]. This has been shown in the mesolimbic area [8] and is accompanied by shifts in the lateralization of monoaminergic activity generally [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, mild acute stress (AS) increased markers of dopaminergic activity in DMS and DLS but only in the left hemisphere in rats showing intact cognitive flexibility [14]. In contrast, chronic unpredictable stress (CUS) increases resting dopamine sensitivity in the substantia nigra pars compacta (SNpc) and reduces the response to rewarding stimuli, causing maladaptive striatal dopaminergic regulation [9]. One of the first neuropeptides released in response to stress is corticotrophin-releasing factor (CRF), which initiates humoral corticosterone release and acts centrally as a neuroregulator of cellular activity [15].…”
Section: Introductionmentioning
confidence: 99%